2019
DOI: 10.12740/app/112014
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use and health behaviors in adolescent residents of urban and rural areas in Poland - a cross-sectional study

Abstract: The aim of the study: This paper attempts to assess Internet addiction and health behaviors in Polish adolescent residents of urban and rural areas. Material and methods: 131 high school students, including 62 (47.3%) residents of rural and 69 (52.7%) residents of urban areas, completed the Polish adaptation of the Problematic Internet Use Test, the Health Behavior Inventory for children and adolescents, and a self-designed survey on the characteristics of Internet use. Results: 28.2% of respondents used the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Similar to other studies [ 18 , 25 ], differences were encountered with the number of hours spent using the Internet for leisure, so that as these increase, AI values increase in the studied sample. Along these lines, problematic use is observed in those individuals who spend an average of 52.7 h per week dedicated to leisure [ 22 ], and yet other studies do not report differences between the addiction of Nursing students to smartphones and the number of hours they use them [ 31 ], although the explanation could be related to the different applications that can be given to this device, such as the time dedicated to making or receiving calls and not just surfing the internet.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar to other studies [ 18 , 25 ], differences were encountered with the number of hours spent using the Internet for leisure, so that as these increase, AI values increase in the studied sample. Along these lines, problematic use is observed in those individuals who spend an average of 52.7 h per week dedicated to leisure [ 22 ], and yet other studies do not report differences between the addiction of Nursing students to smartphones and the number of hours they use them [ 31 ], although the explanation could be related to the different applications that can be given to this device, such as the time dedicated to making or receiving calls and not just surfing the internet.…”
Section: Discussionsupporting
confidence: 82%
“…Individuals who have trouble establishing relationships in real life are at risk of using the internet uncontrollably due to their need for socialization or group membership [ 16 ]. Problematic internet use has been linked to lower mental health and poor sleep quality [ 17 ], reduced time spent with friends and family, increased levels of perceived loneliness [ 16 ], lower engagement in healthy behaviors [ 18 ] and dysfunctional social relationships [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of problematic internet use is higher for individuals that do not engage in physical activities [6]. This is in line with the finding that physical activity positively correlates with individuals' willingness to limit internet use [27]. However, the mean value signified that subjects with no extracurricular activities have more problematic internet use than those engaged in physical activities.…”
Section: Discussionsupporting
confidence: 82%
“…It may be that more affluent students choose leisure activities other than spending time on the Internet, such as going to the cinema, fitness clubs, etc. Our previous research has shown that adolescents, given the opportunity, would choose leisure activities other than spending time online [61]. However, the relationship between socioeconomic status and PIU severity is not a set rule [31,52,62].…”
Section: Piu Vs Age and Gender Materials Statusmentioning
confidence: 99%